Near-Field Ground Motion Modal versus Wave Propagation Analysis - Artur Cichowicz (Shock and Vibration)
The response spectrum generally provides a good estimate of the global displacement and acceleration demand of far-field ground motion on a structure. However, it does not provide accurate information on the local shape or internal deformation of the response of the structure. Near-field pulse-like ground motion will propagate through the structure as waves, causing large, localized deformation. Therefore, the response spectrum alone is not a sufficient representation of near-field ground motion features. Results show that the drift-response technique based on a continuous shear-beam model has to be employed here to estimate structure-demand parameters when structure is exposed to the pulse like ground motion. Conduced modeling shows limited applicability of the drift spectrum based on the SDOF approximation. The SDOF drift spectrum approximation can only be applied to structures with smaller natural periods than the dominant period of the ground motion. For periods larger than the dominant period of ground motion the SDOF drift spectra model significantly underestimates maximum deformation. Strong pulse-type motions are observed in the near-source region of large earthquakes; however, there is a lack of waveforms collected from small earthquakes at very close distances that were recorded underground in mines. The results presented in this paper are relevant for structures with a height of a few meters, placed in an underground excavation. The strong ground motion sensors recorded mine-induced earthquakes in a deep gold mine, South Africa. The strongest monitored horizontal ground motion was caused by an event of magnitude 2 at a distance of 90 m with PGA 123 m/s2, causing drifts of 0.25%–0.35%. The weak underground motion has spectral characteristics similar to the strong ground motion observed on the earth's surface; the drift spectrum has a maximum value less than 0.02%.